Long Non-coding RNA CASC2 Enhances the Antitumor Activity of Cisplatin Through Suppressing the Akt Pathway by Inhibition of miR-181a in Esophageal Squamous Cell Carcinoma Cells - Zhu, Dengyan; Yu, Yang; Qi, Yu; Wu, Kai; Liu, Donglei; Yang, Yang; Zhang, Chunyang; Zhao, Song (Frontiers in Oncology, 2019)
Background: Long non-coding RNA CASC2 (lncRNA CASC2) has been found to be down-regulated in esophageal squamous cell carcinoma (ESCC). However, the effect of CASC2 on cisplatin-treated ESCC was unclear. The present study aimed to evaluate the role of CASC2 in cisplatin-treated ESCC cells. Methods: The expression levels of CASC2 and miR-181a were detected by qRT-PCR. Cell viability was measured by MTT assay. The cytotoxicity effect was detected by lactate dehydrogenase (LDH) release assay. Cell apoptosis was tested by flow cytometry. The protein levels of protein kinase B (Akt) and p-Akt were detected by western blotting. Results: The results showed that CASC2 was low-expressed in ESCC cell lines. Overexpression of CASC2 enhanced the inhibitory effect of cisplatin on cell viability and promoted cisplatin-induced LDH release and apoptosis. We also found that miR-181a expression levels were increased in ESCC cell lines. MiR-181a inhibitor enhanced the antitumor activity of cisplatin, which was similar with the effect of CASC2. CASC2 directly interacted with miR-181a and inhibited the miR-181a expression. MiR-181a reversed the effects of CASC2 on antitumor activity of cisplatin. In addition, we also found that CASC2 suppressed the Akt pathway by inhibiting miR-181a. Conclusions: CASC2 promoted the antitumor activity of cisplatin through inhibiting Akt pathway via negatively regulating miR-181a in ESCC cells. The results provide a new insight for ESCC therapy.